” Aplicación de metodologías de observación directas e indirectas para el monitoreo del zorro andino (Lycalopex culpaeus reissii), para determinar su presencia en la parroquia de Joseguango y Mulaló”. - Cuenca Illaisaca, Alisson Camila (2024)
The Andean fox (Lycalopex culpaeus reissii) is considered the largest canid from South America, it is one from moorland native species, which is commonly called the moorland wolf. The Andean fox, it is seen threatened by different causes, what produces a negative effect to the environment, since this species helps control pests from small mammals, such as the paramo rabbit, it helps to keep balance in the ecosystem, since the Lycalopex culpaeus reissii is a seed dispenser and environmental quality bioindicator. The present study was made with the purpose by knowing the Andean fox presence (Lycalopex culpaeus reissii) in the Joseguango and Mulaló parish; through two stages, the introductory practice and the field stage, which they were placed transects in the Mulaló parish, in the Ticatilin sector, it was drawn three transects with 45 samples, in San Elías two transects with 34 samples and in Ashigua three transects with 47, gettng a total 126 samples, through direct and indirect observation, it using the global positioning, where it was got the signs exact coordinates. Through the anthropic activities file (livestock, agriculture, deforestation, etc.). It is concluded, what in the Joseguango parish, there is greater activity, since it has been urbanized over time, therefore the existence from Andean fox this parish is null. In the three sectors studied Ticatilin, San Elías and Ashigua, there is little anthropic activity, so could be found signs and sightings from Andean fox (Lycalopex culpaeus reissii). In the Joseguango parish and in the three studied sectors from Mulaló, it was not found feral dogs evidence.